December 1970 Special Issue - D'Ambrosio, Charles A. (Journal of Financial and Quantitative Analysis, 1969)
ANALYSIS and listened to the lamentations of countless numbers of colleagues concerning the rate at which the literature is expanding, the field of finance seems to cry out for a precious period of time, however brief it may be, to catch its breath. There appears to be little doubt that keeping up with new ideas, infused into the milieu which is finance, and reincarnated old ideas, clothed in a garb more fitting to the contemporary scene, is at best a most difficult task, especially with the increasing degree of specialization of previously neat and identifiable compartments.